Clients’ Satisfaction with Nursing Services by Using the Patient Satisfaction with Nursing Care (PSNCS): An Applied Research in some of Baghdad Teaching Hospitals - عبد الوهاب نادية لطفي; حاوي محمد مخيلف (Journal of Economics and Administrative Sciences, 2017)
Abstract: This study aims to identify the level of patients’ satisfaction among a sample of hospitalized patients in the targeted hospital (Al-Kindy Teaching Hospital, and Al-Yarmook Teaching Hospital). Moreover, this study highlights the reality of services for patients, especially in the targeted governmental teaching hospitals. The Patient Satisfaction with Nursing Care (PSNCS) has been measured in these hospitals through the revised scale by Tang et al, (2013).This scale includes four major domains; Health Information (5 items), Influencing Support (4 items), Decision Control (4 items), Specialized Technical Competence (7 items). The method of surveying patients’ opinions about the degree of their satisfaction with the nursing services offered in the targeted hospitals. The study scale has been tested for its reliability and validity. The researcher used the statistical measures of Factor Analysis, Mean, Standard Deviation, Kaiser-Meyer-Olkin) exploratory measure, Bartlett Test which measures the association relationships among variables. Moreover, the researcher used the Mann-Whitney test for individual differences among patients’ answers in the targeted hospitals in the Statistical Package for Social Science (SPSS) for Windows . The researcher concluded a set of conclusions, some of which were shared among the targeted hospitals. The most significant conclusions include although the nursing services are delivered in a high-quality professional manner, but the delivery of such services is somewhat delayed from predetermined times which gives the patients an impression of absence of attention with the patients and what they need of care throughout their hospitalization. Furthermore, the nursing staff do not care appropriately in engaging patients in the health care delivered for them, which generates the feeling of absence of interest of the nursing staff with the patients. The researcher suggested a set of recommendations including the necessity of quickening the delivering the nursing services in time in order to substantiate a good impression among patients relative to the extent of their value in the hospital. Additionally, it is vital to take more care of improving the nursing skills for nursing staff through engaging them in specialized courses in order to enhance their competences. Ultimately, it is necessary to quicken the delivery of the nursing services in the appropriate time in order to substantiate a good impression among patients relative to the extent of their value in the hospital.